2015
DOI: 10.1111/dth.12255
|View full text |Cite
|
Sign up to set email alerts
|

Combined oral pulse and topical corticosteroid therapy for severe alopecia areata in children: a long-term follow-up study

Abstract: There are no widely accepted therapy protocols for severe alopecia areata (AA). We treated 65 children/adolescents with AA affecting >30% of scalp. Fourty-three percent of patients had AA plurifocalis (AAP). Fifty-seven percent had AA subtotalis (AAS), AAP+ophiasis (AAP+OPH), and alopecia totalis/universalis (AT/AU). Long-term follow-up (median 96 months) data were available for 69% of patients. Oral dexamethasone (prednisolone 5 mg/kg equivalent) was given once in 4 weeks. Patients received 6, 9, or 12 pulses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 24 publications
1
42
0
6
Order By: Relevance
“…57,66 In children, such effects could impact on their growth and development. 20,64 Therefore, the patient with AA should receive both medical and psychological counseling. The Physician should explain to the patient or patient's parents (when they are children), the unpredictable nature of the condition, the possible course, the treatments available and the success or failure that these may have.…”
Section: Psychological Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…57,66 In children, such effects could impact on their growth and development. 20,64 Therefore, the patient with AA should receive both medical and psychological counseling. The Physician should explain to the patient or patient's parents (when they are children), the unpredictable nature of the condition, the possible course, the treatments available and the success or failure that these may have.…”
Section: Psychological Managementmentioning
confidence: 99%
“…Although corticosteroid pulse therapy has shown lower adverse effects at low doses. 63,64 Methotrexate is being evaluated in children with AT or AU and prednisolone has been recommended in some cases.…”
mentioning
confidence: 99%
“…Systemic corticosteroid therapy in AA was first reported in 1952 by Dillaha and Rothman and steroid pulse therapy by Burton and Shuster in 1975 . The use of contact irritants and steroid‐sparing agents started in the early 1990s . These therapies could have influenced the disease course and long‐term prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of systemic steroids was examined in 13 studies . No studies were found that examined intralesional steroids, likely the result of the extensive nature of AT and AU.…”
Section: Resultsmentioning
confidence: 99%